The Application of E-SAKIP According to Employees' Perspectives in Preparing Performance Accountability Reports: A Case Study at the City of Palu's Department of Public Works and Housing - Rudy Usman; Andi Indriani Ibrahim; Rio Bagas Maulana; Nurdiana; Nurintan Safitri; Nini Andriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the views of employees on the use of the Electronic Government Performance Accountability System (e-SAKIP) application in the preparation of the Government Performance Accountability Report (LAKIP) at the Housing and Settlement Agency (Disperkim) of Palu City. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with employees directly involved in the input and management of the e-SAKIP application. The results of the study indicate that the e-SAKIP application facilitates the visualization of budget realization and performance achievement data, as well as simplifies access to planning and reporting documents. However, the implementation of this application still faces several challenges, such as input errors, the absence of written guidelines, the lack of certified training, and the complexity of the system, which makes it difficult for new employees. Additionally, e-SAKIP has not fully replaced the manual system because the preparation of the LAKIP is still done outside the application. Therefore, e-SAKIP is viewed as a useful reporting tool but still requires improvements to be more effective in supporting the accountability of government agency performance